Othering as mediated soft-power practice: Chinese diplomatic communication of discourse about China-US trade war through the British press. (February 2023) - Tang, Liping
Abstract: This paper examines how Chinese Ambassador to the UK has employed Othering offensive to construct China-US trade war when publishing opinion pieces in the British press to promote China's image and seek partenership. It draws on Discourse-Historical Approach to Critical Discourse Studies. The analysis demonstrates how the Ambassador has used strategies, such as nomination, predication and argumentation, to construct the US as a negative Other to delegitimize its trade policies and actions. Meanwhile, Othering serves as a foil for indirectly constructing a positive Chinese Self as a responsible major country and a positive 'We-group' between China and the US European allies. It sheds some light on understanding the workings of Chinese diplomatic discourse in legitimating China's worldview on 'rules-based international order'. It also contributes to understanding the interplay between the media logic of British/Western press and the soft-power efforts of Chinese/non-Western government. The role of British/Western press in Chinese/counterhegemonic diplomats' mediated soft-power practice is both enabling and constraining.